1970
DOI: 10.3329/jles.v3i0.7440
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Effects of Some Antiseptics and Disinfectants

Abstract: Antimicrobial effects of six antiseptics and disinfectants were studied against five pathogenic bacteria. Different pathogens responded differently to different antiseptics and disinfectants. Antibacterial effects of the antiseptics and disinfectants were also concentration dependent. Formalin and hydrogen peroxide were highly effective against all the pathogens used while phenyl and iodine were least effective. Dettol and Savlon showed moderate antibacterial effects. Key words: Antiseptics; disinfectants; pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 11 publications
1
18
1
2
Order By: Relevance
“…In this case, one would expect an elevated toxicity in the mammals exposed to MA (re: MA-cyanurate or MA-cyanurate-urate crystals). At the same time, Klebsiella species are susceptible to FA; thus, during the concurrent exposures, it is possible that the FA hindered MA conversion in the gut (Saha et al 2009). If this was the case here, there were less MA-derived toxicants available to impart hematologic/immunologic effects in these hosts.…”
Section: Discussionmentioning
confidence: 96%
“…In this case, one would expect an elevated toxicity in the mammals exposed to MA (re: MA-cyanurate or MA-cyanurate-urate crystals). At the same time, Klebsiella species are susceptible to FA; thus, during the concurrent exposures, it is possible that the FA hindered MA conversion in the gut (Saha et al 2009). If this was the case here, there were less MA-derived toxicants available to impart hematologic/immunologic effects in these hosts.…”
Section: Discussionmentioning
confidence: 96%
“…It has been documented that some antiseptics and disinfectants are rather less effective to S. aureus strains that carry a plasmid carrying genes encoding resistance. 27 The study of Saha et al 28 showed similar results in which the effect of six types of antiseptics and disinfectants, namely Dettol (chloroxylenol), Savlon (chlorhexidine gluconate and cetrimide), iodine, phenyl, formalin, and hydrogen peroxide (H 2 O 2 ) was studied on S. aureus, Salmonella typhi, Shigella dysenteriae, Klebsiella species, and E. coli. S. aureus showed the maximum resistance to disinfectants tested.…”
Section: Discussionmentioning
confidence: 87%
“…(chlorhexidine gluconate, 0.3% w/v and cetrimide B.P, 3% w/v), ethyl alcohol (70%), hand gel rub type 1 (ethanol and triclosan), hand gel rub type 2 (ethanol 70% v/v), hand gel rub type 3 (alcohol denat), liquid antiseptic soap types (1, 2 and 3) and plain liquid soap (non-antimicrobial). The sensitivity of the aforementioned agents was evaluated according to Saha et al [14]. Briefly, tryptic soy broth tubes were inoculated with the tested strains and incubated at 37°C for 24 hours.…”
Section: Sensitivity Of Selected Mrsa Isolates To Some Hand Cleansingmentioning
confidence: 99%